The Dynamics of Creative Self-Concept: Changes and Reciprocal Relations Between Creative Self-Efficacy and Creative Personal Identity. Issue 1 (2nd January 2016) - Karwowski, Maciej
Abstract : Although creative self-concept constructs are intensively studied in the creativity literature, little is known about the dynamics of their changes during the life span and the relationships between different aspects of the creative self-concept. Using a longitudinal and a cross-sequential design, this investigation aimed to test changes in two important creative self-concept constructs—creative self-efficacy and creative personal identity—over short (6 months) and longer (20 months) periods of time, while simultaneously examining reciprocal relationships between them. The results showed the short-term stability of both constructs, but they also revealed significant change over the longer period―specifically, a growth of creative self-efficacy and creative personal identity in people from late adolescence to early adulthood and a drop among older participants. Reciprocal longitudinal relationships between creative self-efficacy and creative personal identity were also demonstrated, with creative self-efficacy being a more stable predictor of creative personal identity than the reverse.